A Kinetic Study on the Esterification of Palmitic Acid in Methanol - Kamaruddin, Rose aini; Mohammad Nordin, Nor Asyikin; Buang, Nor Aziah; Ahmad, Saliza (Universiti Putra Malaysia Press, 1998)
The esterification of palmitic acid in excess methanol using thionyl chloride as catalyst has been investigated. It was found that SOCl2 behaved as a good esterification catalyst. The methyl palmitate product obtained has been analysed and characterized using gas chromatography and gas chromatography-mass spectrometry. Optimization studies to determine' the weight percent of catalyst to acid, temperature and time to produce maximum yield of product have also been carried out. The optimum conditions were found to be 0.3% weight of catalyst to acid, 80°C and 2 hours. Subsequently, the rate constants at various temperatures and activation energy of the system were calculated.